The preparation of benzyl esters using stoichiometric niobium (V) chloride versus niobium grafted SiO2 catalyst: A comparison study - Barbosa, Sandro L.; Lima, Camila D.; Almeida, Melina A.R.; Mourão, Larissa S.; Ottone, Myrlene; Nelson, David L.; Klein, Stanlei I. [UNESP]; Zanatta, Lucas D.; Clososki, Giuliano C.; Caires, Franco J.; Nassar, Eduardo J.; Hurtado, Gabriela R. [UNESP] (Elsevier, 2018)
Two solvent free methods of a one-to-one alcohol/acid mol ratio synthesis of benzyl esters of the formic, acetic, benzoic, salicylic, nicotinic, and oxalic acids are described. The stoichiometric reactions used 1.5 mol ratio solid NbCl5 as the reagent and required from two to three hours for completion at room temperature; for the catalytic processes, NbCl5 was grafted directly, at room temperature, onto a silica gel of specific area of 507 m2g−1, produced from construction sand and sodium carbonate, forming a 5.4% Nb w/w SiO2-Nb gel with a specific area of 412 m2g−1. At 10% w/w catalyst/alcohol ratio, this SiO2-Nb catalyst gave similarly very good yields but required from 6 to 9 hours at the reflux temperature of the slurry. The catalyst could be re-used three times.
Keywords: Organic chemistry